CP Violation for B0→ρ0(ω)ρ0(ω)→π+π-π+π- in QCD Factorization - Gang Lü; Jia-Qi Lei; Xin-Heng Guo (Advances in High Energy Physics)
In the QCD factorization (QCDF) approach we study the direct CP violation in B-0→ρ0(ω)ρ0(ω)→π+π-π+π- via the ρ-ω mixing mechanism. We find that the CP violation can be enhanced by double ρ-ω mixing when the masses of the π+π- pairs are in the vicinity of the ω resonance, and the maximum CP violation can reach 28%. We also compare the results from the naive factorization and the QCD factorization.